Analisis penerapan tarif efektif rata-rata dalam perhitungan dan pelaporan Pajak Penghasilan Pasal 21 pada PT Lorent Frozen Fish Kota Bitung - Goenawan, Jestika Estevania Maria; Walandouw , Stanley Kho; Wangkar, Anneke (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to analyse the application of the Average Effective Rate in the calculation and reporting of Income Tax Article 21 at PT Lorent Frozen Fish Bitung City based on PP No. 58 of 2023. This research uses a qualitative method. The types of data in this study are quantitative and qualitative data. The results of this study indicate that PT Lorent Frozen Fish calculates and reports Income Tax Article 21 using the Average Effective Rate based on PP No. 58 of 2023. In the calculation of Income Tax Article 21 there is still an overpayment of tax for employees who stop working in the middle of the year and there are still errors in the application of progressive tax rates for the calculation of annual tax payable. For the reporting of Income Tax Article 21 at PT Lorent Frozen Fish, there is still a delay.